(untitled) (Research, Society and Development, 2022)
The research aims to analyze the competitiveness of the cluster of free-shops in the Fronteira da Paz region (Santana do Livramento-BR and Rivera-UY). The eleven elements of cluster competitiveness proposed by Zaccarelli, et al. (2008) are analyzed. For this, a descriptive analysis is used, with a quali-quantitative approach, through the case study method. Data were collected from secondary data, interviews, questionnaires and observation. The results obtained show that five fundamentals are precisely competitive, these are: geographic concentration, balance without privileged positions, cooperation between companies, selective replacement of businesses and the culture of the community adapted to the cluster. The rest of the six fundamentals are present, but their competitiveness is insufficient, not very dynamic, these are: variety or scope of businesses and institutions, specialization, complementarity through the use of by-products, uniformity of the technological level, evolution through the introduction of new technologies and cluster-oriented outcome strategy. In this way, it is possible to draw up strategies to strengthen the present fundamentals and develop those of insufficient performance.